DEVELOPMENT OF TISSUE CULTURE PROTOCOL FOR MASS PRODUCTION OF STEVIAREBAUDIANA (BERTONI) BERTONI - Mubashrah Munir; Ishrat Fatima; Beenish Aftab; Ali Ahmed Sheikh; Arshia Shabir; Jamshaid Ahmad; Muhammad Saeed Ahmed (Journal of Animal and Plant Sciences, 2023)
Steviarebaundiana is containing sweet phytochemicals and is a zero-caloric natural alternative to artificial sweeteners. The direct organogenesis of S.rebaundiana was carried out using apical bud explant invitro. The Murashige and Skoog medium was used and the culture was set up under optimized conditions of 24±2°C temperature, and 16 hours of light exposure with cool, white fluorescent light. The seven different concentrations of benzylaminopurine (BAP) and IAA (Indole-3-acetic acid) (0.01, 0.02, 0.03, 0.04, 0.05, 0.06 and 0.07mg/L) were employed for shoot development and root development respectively. The results revealed that of all the tested concentrations of BAP used for shoot development, 0.07mg/L proved to be best for shoot initiation after 6 days of culture. On the other hand, the suitable concentration of IAA at which root initiation was observed after 7 days of subculture, was 0.06mg/L. The study can be beneficial for the researchers, food industry and growers for commercial production of the S.rebaudiana nursery.
Keywords: Direct organogenesis; Mass production; Medicinal plant; Steviarebaudiana; Tissue culture